PENGARUH KONSELING KELOMPOK TERHADAP PRESTASI BELAJAR DALAM MASA PANDEMI COVID-19 - Yohana Nurung; Nuraeni Nuraeni; Lalu Jaswandi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT The decline in students’ academic achievement during the COVID-19 pandemic reflects a gap between academic demands and students’ psychological readiness, highlighting the need for appropriate counseling-based interventions. This study aims to analyze the effect of group counseling on improving the academic achievement of eleventh-grade students at SMKPP Negeri Mataram in the 2021/2022 academic year. An experimental approach was employed using a one-group pre-test–post-test design focusing on students identified as having low academic achievement as the intervention subjects. Data were collected through pre-test and post-test measures of academic achievement, and analyzed using a t-test. The results indicate that the calculated t-value (5.474) is higher than the t-table value (2.447) at a 5% significance level with 6 degrees of freedom, demonstrating a significant improvement in students’ academic achievement after the implementation of group counseling. Substantively, this improvement suggests that group dynamics, social interaction, and emotional support within the counseling process contribute to enhanced student motivation and learning engagement. Therefore, it can be concluded that group counseling has a significant effect on improving students’ academic achievement. The findings imply the importance of optimizing group counseling services as an adaptive intervention strategy to address learning challenges during crisis situations and provide practical guidance for school counselors in designing more effective and contextual services. ABSTRAK Rendahnya prestasi belajar siswa selama pandemi COVID-19 mencerminkan adanya kesenjangan antara tuntutan akademik dan kesiapan psikologis siswa, sehingga diperlukan intervensi yang tepat dan berbasis layanan bimbingan konseling. Penelitian ini bertujuan untuk menganalisis pengaruh konseling kelompok terhadap peningkatan prestasi belajar siswa kelas XI di SMKPP Negeri Mataram Tahun Pelajaran 2021/2022. Pendekatan yang digunakan adalah eksperimen dengan desain one group pre-test–post-test yang difokuskan pada siswa dengan prestasi belajar rendah sebagai subjek intervensi. Teknik pengumpulan data menggunakan tes prestasi belajar sebelum dan sesudah perlakuan, sedangkan analisis data dilakukan dengan uji t (t-test). Hasil analisis menunjukkan bahwa nilai t-hitung sebesar 5,474 lebih besar dibandingkan t-tabel sebesar 2,447 pada taraf signifikansi 5% dengan derajat kebebasan (db) = 6, yang mengindikasikan adanya peningkatan prestasi belajar setelah diberikan layanan konseling kelompok. Secara substantif, peningkatan ini menunjukkan bahwa dinamika kelompok, interaksi sosial, serta dukungan emosional dalam proses konseling berkontribusi terhadap peningkatan motivasi dan keterlibatan belajar siswa. Dengan demikian, dapat disimpulkan bahwa konseling kelompok berpengaruh signifikan terhadap peningkatan prestasi belajar siswa. Implikasi penelitian ini menegaskan pentingnya optimalisasi layanan konseling kelompok sebagai strategi intervensi yang adaptif dalam mengatasi dampak pembelajaran pada masa krisis, serta dapat menjadi rujukan bagi guru BK dalam merancang layanan yang lebih efektif dan kontekstual.